Heterotopic Prostate at Autopsy- An Unusual Mass at the Dome of the Urinary Bladder - Munde, Shital (J Clin Diagn Res, 2017)
Heterotopic prostate in the dome of the urinary bladder is extremely rare and difficult to diagnose. It is often mistaken for neoplastic masses and histopathological examination is warranted for diagnosis. We report an autopsy case of an ectopic prostate at the dome of the bladder which mimicked a neoplasm on gross pathology.